Conceptions of Solidarity - Hubmann, Georg; Kapeller, Jakob (Momentum Quarterly, 2012)
The term „solidarity“ is notoriously ambigious, especially its German equivalent „Solidarität“, whose meaning and potential implications is discussed in this paper. This ambiguity in turn raises the obvious question whether the blurred concept of solidarity is really suitable as a normative reference point for shaping individual actions or political decisions. We try to contribute to an answer to this question by differentiating between several concepts of solidarity, which differ with respect to the arguments used to legitimize and concretize expressions of solidarity. In turn we apply these different conceptualizations of solidarity to three major political questions (gender equality, trade union policies and development cooperation) and compare the different political strategies arising from these distinct understandings of solidarity. Finally, we ask for the conditions necessary to employ a progressive conceptualization of solidarity, which aims to integrate several aspects of the before mentioned conceptualizations of solidarity.